Testing the Role of Adolescent Sexual Initiation in Later-Life Sexual Risk Behavior - Huibregtse, Brooke M.; Bornovalova, Marina A.; Hicks, Brian M.; McGue, Matt; Iacono, William (Psychological Science, 2011)
The consistent association between adolescent sexual initiation (ASI) and risky adult sexual behavior (RASB) has generally been assumed to indicate that ASI has a causal effect on RASB; consequently, it is assumed that delaying ASI will reduce RASB. Yet the ASI-RASB association might be better accounted for by some third variable. We evaluated the causal role of ASI (initiation of oral, anal, or vaginal sex at or before age 16) in influencing RASB in a longitudinal sample of 2,173 twins (followed from ages 11 to 24 or from ages 17 to 29) using two methods: the discordant-twin design and the propensity-score design. The former controlled for unmeasured genetic and shared environmental factors, and the latter controlled for measured nonshared environmental factors. We replicated the link between ASI and RASB reported in previous research, but results from the discordant-twin and propensity-score analyses suggested that this association is better explained by common genetic or environmental risk factors than as a causal effect. These findings suggest that preventing ASI is unlikely to reduce RASB.